Contact endoscopy as a novel technique in the detection and diagnosis of oral cavity and oropharyngeal mucosal lesions in the head and neck. Issue 2 (February 2014) - Dowthwaite, S; Szeto, C; Wehrli, B; Daley, T; Whelan, F; Franklin, J; Nichols, A; Yoo, J; Fung, K
Abstract Objective: We aimed to investigate the diagnostic accuracy of contact endoscopy in evaluating oral and oropharyngeal mucosal lesions. Methods: Between January 2010 and December 2011, 34 patients with lesions of the oral and oropharyngeal mucosa were enrolled in the study. Comparison between initial contact endoscopy results and 'gold standard' tissue biopsy was undertaken. Results: Nine patients had histologically confirmed squamous cell carcinoma, 2 had carcinoma in situ, 3 had dysplastic lesions and 20 patients had various benign lesions. Contact endoscopy demonstrated sensitivity and specificity of 89 and 100 per cent respectively in the evaluation of malignant lesions. Benign lesions were correctly categorised in 50 per cent of cases (10/20). The video images from contact endoscopy could not be interpreted in six cases. Conclusions: Contact endoscopy demonstrates high sensitivity and specificity in the imaging of malignant lesions with reduced reliability in the evaluation of benign lesions. Significant shortcomings also exist in the design of current technology that we believe represent a significant barrier to the reliable collection of useful video data.